Exposure at Default Modeling with Default Intensities - Jiří Witzany (European Financial and Accounting Journal, 2011)
The paper provides an overview of the Exposure at Default (EAD) definition, requirements, and estimation methods as set by the Basel II regulation. A new methodology connected to the intensity of default modeling is proposed. The numerical examples show that various estimation techniques may lead to quite different results with intensity of default based model being recommended as the most faithful with respect to a precise probabilistic definition of the EAD parameter.
Keywords: C14; G21; G28; 650; Credit risk; Exposure at default; Default intensity; Regulatory capital